Acting towards a sustainable society - Nordström, Niko (Taideyliopiston Teatterikorkeakoulu, 2026)
The aim of this thesis is to find a personal and collective practice to deepen the relation to nature through methods I’ve found useful as an actor. The means to achieve that are twofold, first personal explorations which I then reflect upon and a shared practice which I open through facilitated case studies involving a focus group using methods that derive from an acting practice. The philosophical grounds I root this research aim in, is Deep Ecology. I use the concept of situated writing together with reflective writing to first find out how places affect me and how the experiences linger on in reflections. To achieve this, I’ve maintained a writing practice of blogging. I then enter a dialogue with my blog posts through the academic reflexivity that the process of writing this thesis offers. It is by using the knowledge of my profession and education as an actor, through the combination of the Chekhov technique and Viewpoints in relation to site-specific outdoor locations, in a practice I’ve coined eco-Chekhov, that I aim to create new meanings and stronger bonds with our surroundings. The exercises are also practical for opening the research and as a methodology to survey the distinctions between places and their affects. I’ve used discussions during and after case studies and written surveys as feedback gathering methods to map out how a collective ecologically rooted acting practice could seem. The combination of writing and acting practices found have personally shaped a sustainable method to use in my career post-graduation.
Keywords: syväekologia; urbaani löytöretkeily; psykogeografia; Deep ecology; Urban exploration; Psychogeography; Chekhov; Tjehov; Tšehov, Anton; kestävä kehitys; näytteleminen; opetus; teatteritaide; näyttelijät; luontosuhde; kirjoittaminen; luova kirjoittaminen; tieteellinen kirjoittaminen; blogit; taiteellinen tutkimus; tapaustutkimus; luolat; fi=ruotsinkielinen näyttelijäntaide|sv=skådespelarkonst på svenska|en=Acting in Swedish|